Formal analysis based evaluation of software defined networking for time-sensitive Ethernet - Thiele, Daniel; Ernst, Rolf (Proceedings - Design, Automation, and Test in Europe Conference and Exhibition, 2016)
Software defined networking (SDN) aims to standardize the control and configuration of network infrastructure. It consolidates network control by moving the network's control plane to a (logically) centralized controller and downgrading switches to simple forwarding devices. This offers huge advantages for future automotive Ethernet networks, including admission control (e.g. to prevent/limit congestion) or network reconfiguration (e.g. in case of faults), both based on a centralized view of the current network state. SDN's centralized architecture, however, requires additional communication, which entails a certain overhead. If SDN is used in safety-critical real-time networks, this communication is subject to strict timing requirements. In this paper, we present a formal analysis based evaluation of the general suitability of SDN for time-sensitive networks including overhead, scalability, and timing guarantees by using a realistic automotive setup.